The IDEAL prospective development study format for reporting surgical innovations. An illustrative case study of robotic oesophagectomy - Diez Del Val, I; Loureiro, C; McCulloch, P (Elsevier, 2015)
Background: The early development of innovative surgical procedures is usually reported as retrospective case series, wasting opportunities to provide useful information and introducing bias. We present a report of an innovative procedure in development, using the Prospective Development Study (PDS) format recommended by the IDEAL Collaboration. Methods: We report the development of robotically assisted oesophagectomy by a two-surgeon team from the first robotic case onwards. Key outcomes (blood loss, robotic operating time, lymph node yield, length of stay and complications) are prospectively reported for each patient sequentially. Reasons for rejecting cases for robotic surgery are explained. All changes to technique or indication are highlighted, showing when they occurred and explaining why they were instituted. Results: The first robotic oesophagectomy was attempted in December 2009. Subsequently 55 oesophagectomies were undertaken, 34 using the robot and 21 without it. Seven deliberate changes in technique occurred during the series. Nodal yield increased markedly after adopting formal mediastinal node dissection and clipping of the thoracic duct. No obvious trends were noted in other outcomes. The robot facilitated Intra-thoracic anastomosis, but mediastinal node dissection showed no advantages due to loss of haptic sensation. Complication rates, R0 rates and nodal yield were considered acceptable. Discussion: Presenting the development experience in this way improved the clarity of transmission of the main learning points for other surgeons, eliminated bias from selective reporting and explained other types of selection bias. The IDEAL Prospective Development Study has clear advantages over standard case series format for presenting uncontrolled early study data from innovative procedures.